Saladin, the Almohads and the Banū Ghāniya : the contest for North Africa (12th and 13th centuries) - Baadj, Amar Salem. (Studies in the History and Society of the Maghrib, 2015)
In Saladin, the Almohads and the Banū Ghāniya , Amar Baadj gives us the first comprehensive, modern study of a fascinating but little-known episode in the history of the medieval Mediterranean. This is the story of the long struggle between the Almohad caliphs of the Maghrib, the Banū Ghāniya of Majorca, and the Ayyubids for dominance of North Africa. The author makes use of important textual sources that have been ignored as well as new archaeological evidence to challenge some of the basic assumptions about the events in question. He also successfully places these events in their wider temporal and geographical context for the first time.